PROTECTION LAW TO VENDORS RELATED TO THE USE OF BEAUTY CONTESTS IN PROCUREMENT OF GOODS AND SERVICES BY BUMN - Putra Hsb, Ibnu Habib Ryandi Syah; Ginting, Budiman; Sunarmi, Sunarmi; Siregar, Mahmul (NOMOI Law Review, 2023)
KPPU stated that 80 percent of tender problems in Indonesia related with beauty contest . Lots of it report as well as case proves that there are no clear rules regarding the implementation of beauty contests in tender arrangements in Indonesia, giving rise to allegations of collusion within them. Example, PT. Pertamina (Persero) and PT. Medco Energi International, Tbk, suspected of having committed collusion. In case According to KPPU, it is a tender process. In its decision, the KPPU stated that PT Pertamina and PT Medco Energi Internasional and Mitsubishi Corporation were proven to be the winners of the beauty contest. This research uses normative juridical research methods that are qualitative in nature. The beauty contest method is vulnerable to irregularities and collusion due to its closed nature and each provider of goods or services/vendors cannot know who their competitors are. And No There is reject measuring Which clear related appointment winner beauty contest Position vendors in beauty contest in BUMN Not yet Enough protected, because there is no clear legal basis for the implementation of procurement of goods and services by BUMN using a beauty contest .